Mathematical representation ability of class VII students on ARIAS learning model viewed from self-renewal capacity - Ula, Nurul Afifatul; Dewi, Nuriana Rachmani (Unnes Journal of Mathematics Education, 2021)
This study aims to describe: 1) The effectiveness of the ARIAS learning for mathematical representation ability; 2) The ability of mathematical representation viewed from Self-Renewal Capacity (SRC). The method used is mixed methods with a population of class VII students of SMP N 40 Semarang 2019/2020 school year. Samples were taken by random class technique, obtained VII C as an experimental class and VII B as a control class. Subjects were taken using the purposive sampling technique, and 9 subjects were selected based on the student’s SRC category. The methods of data collection using tests, questionnaires and interviews. The results showed that (1) ARIAS learning was effective against MRA; (2) Subjects with high SRC tend to meet all indicators of MRA; subjects with moderate SRC, S-04 and S-05 tend to meet all indicators of MRA, S-06 were less able to write down the steps for solving mathematical problems in words; Subjects with low SRC, S-07 was less able to create mathematical equations or models from the representations given and write down the steps for solving mathematical problems in words, S-08 and S-09 were unable to create mathematical equations or models from the representations given and write down the steps for solving mathematical problems in words.